Professional Doctorates and Emerging Online Pedagogies - Banks, Sheena; Joyes, Gordon; Wellington, Jerry (Proceedings of the International Conference on Networked Learning, 2008)
The development and implementation of networked learning within postgraduate programmes is increasing, but there is emerging evidence that the use of networked technology within these programmes is creating specific challenges that reflect the cultural, professional and educational expectations of students as they develop expertise in research, particularly in the case of the professional doctorate. The implications of using networked technology for the development of communities of practice of researchers have not yet been fully identified nor understood nor have its benefits been explored. In this paper, we address these issues by presenting a case study of the development of interactive online research narratives as the basis for the teaching of research methods in professional doctorate programmes. New technology and networked learning has had to date a surprisingly limited impact on teaching and learning practice within professional doctorate programmes. Learning technology has been identified by a number of researchers as having potential to bring more flexibility into the learning and teaching of research methods. Despite the existence of considerable distance learning provision supporting remote location students, however, there is not much evidence that this is happening. We argue that networked learning has the potential to change the pedagogic practice of professional doctorates, not only through flexible learning in relation to time, place, topics and use of resources, but also for the development of higher order knowledge and metacognition where we can involve students in rich interactions with peers and more experienced researchers and engagement with authentic examples and insights about practice We will present outcomes from the V-ResORT Project (Virtual Resources for Online Research Project to address these issues. This work has been funded by the Higher Education Funding Council for England (HEFCE) over a three year period from 2004-7. The V-ResORT Project has developed innovative online learning materials that provide video narratives of researchers exploring key questions connected with their work. These narratives are displayed using the MS Producer video streaming software as a series of short 3-5 minute clips in higher resolution alongside PowerPoint slides and a transcript that enable the user to easily navigate through a complete narrative and provides them with support for the often complex language used within research methodology. We will give a demonstration of some clips of video narratives that capture effective practice as case studies of use. We will briefly discuss the theoretical framework for the context of use in professional doctorate programmes and for developing the video narratives. We will draw on empirical data to present evidence of how we achieved this, particularly in attempting to embed capabilities within the online materials of reusability and personalisation, the relationship between these and student feedback. Our strategies for reusability have resulted in new scenarios of use, for example the development of a Virtual Graduate School.